A new species of Tamenes Gounelle, 1912 (Coleoptera, Cerambycidae) - Bezark, Larry G.; Santos-Silva, Antonio; Galileo, Maria Helena M. (Zootaxa, 2016)
After the original description of Tamenes sarda Gounelle, 1912, based on a single male from Panama, the species was rarely mentioned in the literature except in catalogues and checklists. An exception appeared in Monné & Martins (1973) who speculated that Palaeotrachyderes Tippmann, 1960 may be equal to Tamenes (translated): “In 1960 Tippmann described Palaeotrachyderes, relating it with Lissonotini. The type species, P. laticornis, is also from Chiriqui [the type locality of T. sarda]. Those facts lead us to assume that the genera may be very close or even synonyms, which must be proven upon examination of material of that area.” However, the scutellum of P. laticornis is notably small, while in T. sarda it is distinctly large. This feature makes it unlikely that those genera are synonymous.